Interaksi Wilayah di Kawasan Strategis Nasional (Perbatasan) dalam Kerangka Jaringan Perkotaan - Syaiful Muazir (Jurnal Wilayah dan Lingkungan, 2019)
To support the development of lagging areas (border areas), the Government of Indonesia has encouraged urban areas in the border to become strategic areas with certain development priorities. These specified areas could become a growth center for "transferring" the development outputs to the other areas. One of the border regency in West Kalimantan Province is Sambas Regency. There are two categories of "strategic areas" in this regency, that is Sambas District (the regency’s capital city) as a tourism strategic area, and border area (Temajuk and Aruk) as the National Strategic Activities Center. Expectedly, these two strategic areas could interact more balanced and equally in regional development. This research deals with preliminary exploration which aims to identify the tendency of regional interaction in the strategic areas. Interaction is considerably important for the lagging areas in the border to  distribute development outputs from other areas. This study applies the principle approach of network analysis by using different network types such as technical networks (infrastructure), transactional networks, and social networks. The results show that the interaction between developed and lagging areas has not been optimal yet. Sambas District is more attracted to the south closing to the provincial capital city while the border areas more attached to neighboring countries as well as other advanced (internal) areas next to the border.